Whole-genome copy-number analysis identifies new leads for chromosomal aberrations involved in the oncogenesis and metastastic behavior of uveal melanomas. Issue 3 (June 2015) - van Engen-van Grunsven, Adriana C.H.; Baar, Marjolein P.; Pfundt, Rolph; Rijntjes, Jos; Küsters-Vandevelde, Heidi V.N.; Delbecq, Ann-Laure; Keunen, Jan E.; Klevering, Jeroen B.; Wesseling, Pieter; Blokx, Willeke A.M.; Groenen, Patricia J.T.A.
<x xml:space="preserve">Abstract</x> To further elucidate the genetic underpinnings of uveal melanoma (UM) and identify new markers that correlate with disease outcome, archival formalin-fixed, paraffin-embedded enucleation specimens from 25 patients with UM and a mean follow-up of 14 years were analyzed for whole-genome copy-number alterations using OncoScan analysis. Copy-number alterations of chromosomes 1, 3, 6, and 8 were also analyzed in these tumors using multiplex ligation-dependent probe-amplification, and mutations in GNAQ, GNA11, and BAP1 were searched for by Sanger sequencing. Our study confirms the previously reported GNAQ and GNA11 mutation frequencies in UMs as well as the presence of monosomy 3 as a factor strongly indicating poor prognosis. Two cases with metastatic disease, but without monosomy of chromosome 3, showed loss of a small region in the distal part of chromosome 2p. Also, UMs leading to metastatic disease had more chromosomal aberrations than those without metastases. Three UMs lacking a GNAQ or a GNA11 mutation showed a gain of chromosome 8q; one of these cases showed extensive chromothripsis. Another case (with suspect lung metastasis) showed focal chromothripsis. Our whole-genome copy-number analysis shows that focal loss of chromosome 2p may be involved in the metastatic spread of UMs without monosomy 3; metastatic UMs carry more chromosomal aberrations than those without metastases; and chromothripsis may play a role in the oncogenesis of UMs, but does not necessarily indicate a poor prognosis. The clinical and particularly diagnostic utility of these findings needs to be corroborated in a larger set of patients with UM.